أثر مواقع التواصل الاجتماعي - لطفي علي قشمر, على (جامعة الوادي - University of Eloued, 2020)
هدفت الدراسة إلى التعرف على أثر مواقع التواصل الاجتماعي على حدوث الخلافات الزوجية من وجه نظر المتزوجين العاملين في الجامعات الفلسطينية، إضافة إلى تحديد أثر متغيرات النوع الاجتماعي، العمر، مكان السكن، والمؤهل العلمي. تكون مجتمع الدراسة من المتزوجين مستخدمي مواقع التواصل الاجتماعي في الجامعات الفلسطينية، حيث أجريت الدراسة على عينة قوامها (160) من المتزوجين مستخدمي مواقع التواصل الاجتماعي في الجامعات الفلسطينية، وتم اختيارهم بطريقة عشوائية، وقد تكونت الاستبانة من (28) فقرة موزعة إلى أربعة أبعاد، ووجد أن معامل ثبات أداة الدراسة كان (0.88) وهي نسبة تؤكد إمكانية استخدام الأداة لأغراض الدراسة. Abstract: The study aimed to identify the impact of social networking sites on the occurrence of marital differences from the perspective of married couples working in Palestinian universities, in addition to determining the impact of gender variables, age, place of residence and scientific qualification. The study population consisted of married users of social networking sites in Palestinian universities. The study was conducted on a sample of(160) married persons who used social networking sites in Palestinian universities. They were randomly selected. The questionnaire consisted of 28 paragraphs divided into four dimensions. It was found that the coefficient of stability of the study instrument was(0.88) which confirms the possibility of using the tool for study purposes.
مقال
Keywords: مواقع التواصل الاجتماعي ; الخلافات الزوجية ; المتزوجين ; الجامعات الفلسطينية; Social networking sites; marital disputes; married couples; Palestinian universities